2022
DOI: 10.1002/ceat.202100435
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly Technique for Preparation of ZnO Nanoparticles: Pd(II) Ions Adsorption

Abstract: A novel eco-friendly procedure was developed to adsorb Pd 2+ ions from wastewaters using the green synthesized zinc oxide (ZnO) nanoparticles (NPs). ZnO NPs were easily produced using zinc nitrate through Centaurea cyanus extract as a reducing agent at ambient conditions. X-ray diffraction results demonstrated that ZnO NPs have a highly crystalline hexagonal structure. Fourier transform infrared spectral analysis indicated an active contribution of C. cyanus-derived biomolecules in zinc ions bioreduction. ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…However, it is not recommended to conclude on the chemical or physical nature of adsorption based on the good fit of the Langmuir or Freundlich model alone, rather a reliable conclusion would involve a holistic consideration of the isotherm, kinetics thermodynamics, desorption, and mechanistic interpretations. Furthermore, the favorability of the adsorption process or efficient interaction between the metal ions in solution and ZnONPs can be deduced from the Freundlich n value in the range of 1-10 (Chukwuemeka-Okorie et al 3, it is observed that the values of n obtained for heavy metals and radionuclides adsorption were all in the favorable range except for a few studies involving the adsorption of Cu(II), Pb(II) and Pd(II) (Somu and Paul 2018;Primo et al 2020;Leiva et al 2021;Davarnejad and Nikandam 2022). This shows that metal contaminants in water and ZnONPs have a good affinity for efficient water decontamination.…”
Section: Adsorption Isotherm Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not recommended to conclude on the chemical or physical nature of adsorption based on the good fit of the Langmuir or Freundlich model alone, rather a reliable conclusion would involve a holistic consideration of the isotherm, kinetics thermodynamics, desorption, and mechanistic interpretations. Furthermore, the favorability of the adsorption process or efficient interaction between the metal ions in solution and ZnONPs can be deduced from the Freundlich n value in the range of 1-10 (Chukwuemeka-Okorie et al 3, it is observed that the values of n obtained for heavy metals and radionuclides adsorption were all in the favorable range except for a few studies involving the adsorption of Cu(II), Pb(II) and Pd(II) (Somu and Paul 2018;Primo et al 2020;Leiva et al 2021;Davarnejad and Nikandam 2022). This shows that metal contaminants in water and ZnONPs have a good affinity for efficient water decontamination.…”
Section: Adsorption Isotherm Modelingmentioning
confidence: 99%
“…Zinc oxide nanoparticles (ZnONPs) in particular have attracted a lot of attention among nanoparticle adsorbents because of their biocompatibility, affordable price, long-term stability, surface characteristics, photocatalytic activity, nontoxicity, and powerful antibacterial activity against microbes often found in water (Akbar et al 2019;Gu et al 2020;Akpomie et al 2021). As a result, various studies on the adsorption of heavy metals and radionuclides onto ZnONPs have been conducted (Kumar et al 2013;Kaynar et al 2014;Azizi et al 2017;Lagashetty et al 2020;Gu et al 2020;Alqahtany and Khalil 2021;Davarnejad and Nikandam 2022). Due to the importance of ZnONPs in water treatment, a review of their capability as a water decontaminating agent via adsorption and photocatalysis was written (Bharti et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the presence of a huge reduction potential that hampers the transfer of electron molecules between the donor molecule (NaBH 4 ) and the acceptor (dye molecule). When a small quantity of nano-catalyst was put into the catalytic reaction, the rate of the reaction was accelerated and the degradation reaction was made kinetically favorable [27]. The viability of degradation with the pure plant extract, without the nano-catalyst, was also evaluated in the dye degradation process (Supporting Information Fig.…”
Section: Degradation Of Textile Dyesmentioning
confidence: 99%